Hospital readmission after anterior cruciate ligament reconstruction: protocol for a systematic review and meta-analysis. Issue 10 (16th October 2020) - Shao, Long; Wu, Di; Li, Jia-Ying; Wu, Xiang-Dong; Zhou, Xi; Qiu, Gui-Xing; Luo, Changqi; Xiao, Peng-Cheng; Liu, Jia-Cheng; Huang, Wei
Abstract : Introduction: Anterior cruciate ligament (ACL) injury is one of the most common injuries of the knee. ACL reconstruction (ACLR) has been widely performed as a safe and effective treatment for ACL injuries. As there is an increasing trend in the incidence of ACL injury, hospital readmission after ACLR has attracted renewed attention for the financial burden to both patients and the healthcare system. However, information about hospital readmission after ACLR remains fragmented. Therefore, we plan to systematically review the literature to investigate the rate of, causes and risk factors for hospital readmission after ACLR, and summarise interventions to reduce hospital readmission. This article is to provide the protocol for an upcoming systematic review and meta-analysis on this important issue. Methods and analysis: Reporting of this protocol follows the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) checklist. Electronic databases, including PubMed, Embase and the Cochrane Library, will be systematically searched from inception to June 2020. No language restrictions will be applied. Studies will be included if they reported hospital readmission or explored the associated potential causes and risk factors for hospital readmission after ACLR. The primary outcome will be the number and time frame of hospital readmission after ACLR. Secondary outcomes will be reasons for readmission, number and types of complications, risk factors for readmission and preventive measures for readmission after ACLR. Quality assessments will be performed by using the Newcastle-Ottawa Scale (NOS). If possible, study results will be summarised in a forest plot, and heterogeneity will be tested by using the Cochran's Q and I 2 statistics. Ethics and dissemination: No ethical approval is required because our study is not related to patients or animals. The results will be published in a peer-reviewed journal. PROSPERO registration number: CRD42020058624.